PERENCANAAN SISTEM PENDINGIN UDARA MENGGUNAKAN CEILING DUCT DENGAN PENGATURAN SISTEM VRV/F PADA GEDUNG PERKANTORAN 3 LANTAI - Srihanto; Moch Sugiri (JTTM : Jurnal Terapan Teknik Mesin, 2021)
In tropical countries, there is a need for air conditioning systems, especially for high-rise buildings to provide comfort for their residents. For this reason, it is necessary to plan an air conditioning system using a ceiling duct with a VRV / F (Variable Refrigerant Volume / FLOW) system setting so that the load and capacity are appropriate and more efficient. In calculating the cooling load, starting from the sensible load and the load, and calculating the size of the ducting. The research method used to plan an air conditioning system using a ceiling duct with VRV / F system settings is the observation method by taking the required data. Perform calculations and analysis with the data obtained. So that after planning the total load on the 5th floor = 270,752.79 Btu / hr (79.3498kW), the 6th floor = 280,568.37 Btu / hr (82,227 kW), and the 7th floor = 229,690.66 Btu / hr (67.3157kW). The size of the ducting supply used is: Height = 75mm-450mm, Width = 75mm - 450mm and the size of the ducting return used is Height = 75mm-450mm, Width = 75mm-450mm. From the planning results, it is determined that the air conditioning system uses a ceiling duct system with VRV / VRF system settings. The advantages are Easy Maintenance, high reliability, large capacity use, space-saving design, different indoor units in one system, and using R410 type refrigerant.